Analysis of The Effectiveness of The Implementation of Bridge Resource Management On Shipping Safety - Sutan Dijavantha; Capt. Firdaus Sitepu; Intan Sianturi; I'ie Suwondo (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
As a busy shipping route, Indonesia experiences a high number of maritime accidents caused by human factors such as miscommunication and fatigue; therefore, the implementation of Bridge Resource Management (BRM) needs to be evaluated to ensure maritime safety. This study aims to analyze the effectiveness of BRM through responsibility, crew skills, and performance improvement efforts on the bridge of the MV ABM Nubiri. Using a descriptive qualitative approach, the population consisted of the entire bridge crew (17 people), with a purposive sample of three key informants (Captain, Chief Officer, and Helmsman). Research instruments included semi-structured interviews, participant observation, and documentation; analysis was conducted using the Miles-Huberman interactive method with triangulation. Results indicated clear task division, effective communication through repeated commands, and good situational awareness; however, these were hindered by fatigue and low participation from junior crew members. Conclusion: BRM is effective but requires routine training and fatigue management to optimize safety.